Woman-centred ethics: A feminist participatory action research. (February 2023) - Buchanan, Kate; Geraghty, Sadie; Whitehead, Lisa; Newnham, Elizabeth
Abstract: Introduction: Contemporary ethical issues in the maternity system are nuanced, complex and layered. Medicalisation and the reported rise in incidence of mistreatment and birth trauma, has been described as unethical. Some authors suggest bioethical principles are limited in terms of guiding everyday care of pregnancy and birth. There is currently no known published research which explores what birthing people say is ethical. Aims: This study sought to explore women's experience of maternity care from an ethical perspective. Method: A Feminist Participatory Action Research (FPAR) was conducted over three years, in two phases. A Community Action Research Group (CARG) was formed of nine participants, and data were captured from five focus groups. A further ten participants were recruited for individual in-depth interviews, the data corpus was combined, and thematic analysis was applied. All 19 participants had experienced a midwifery model of care in Western Australia. Results: A unique ethical perspective was described by the participants. The central theme: 'Radical desires: Individuals values and context' placed the woman at the centre of the care, in determining what is ethical. Two categories captured the care experienced: Woman-centred ethics or Authoritarian ethics. A conceptual model Woman-centred ethics is offered to enhance everyday ethical midwifery care. Discussion: The participants in this study perceived care as either ethical or unethical based on the quality of the relationship, the knowledge that was shared and the manner of the care given. The Woman-centred ethics model may be a starting point for moving the field forward in ethical discussion.